EDTA‐dependent pseudo thrombocytopenia mimicking dengue fever‐associated persistent thrombocytopenia: A case report - Gentle Sunder Shrestha (Wiley, 2021)
Abstract No hemorrhagic manifestations, presence of platelet clumps on the peripheral blood smear, normal manual count, and normal autoanalyzer count after collecting blood in citrate vial help confirm the diagnosis of EDTA‐dependent thrombocytopenia.